Artificial Intelligence in the Dutch Press: An Analysis of Topics and Trends. Issue 3 (26th May 2020) - Vergeer, Maurice
ABSTRACT: The present study focuses on newspaper articles published in all newspapers in the Netherlands from 2000 up to 2018 on how they report on artificial intelligence. The study showed how reporting changes over time and how different types of newspapers report differently about various topics in the field of artificial intelligence. The findings show that newspapers increasingly report about AI from 2014 onward. Newspapers do so on a wide range of topics related to AI. Several types of newspapers showed distinct coverage of many artificial intelligence-related topics. Although robots and their football capabilities appear to be ever-present in newspapers, recent articles about tech giants and fake news are more prominent in newspapers. One of the most notable findings was that religious newspapers published less about AI topics, even though some topics on artificial intelligence have religious connotations (cf. singularity, consciousness). Sentiments about AI in newspaper articles remained balanced between positive and negative sentiments over the years.